Theory Construction and Model-Building Skills: A Practical Guide for Social Scientists - Brandy Pratt (The Evaluation Center at Western Michigan University, 2010)
A review of the book Theory Construction and Model-Building Skills: A Practical Guide for Social Scientists by James Jaccard & Jacob Jacoby published in 2010 by Guilford.